From the experience of universal learning actions usage during the class - Musaybekov R. K. (Interactive science, 2016)
the author describes some theoretical aspects of universal learning activities and they are shown in examples in this article. It describes the relationship between theoretical and practical materials.
Keywords: универсальные учебные действия; компетентность; толерантность; саморазвитие; самосовершенствование; self-development; профессиональное развитие; tolerance; competence; согласие; professional development; социальная консолидация; universal education actions; self-improvement; agreement; social cohesion and harmony